ASSIMETRIA DE INFORMAÇÕES E PAGAMENTO DE DIVIDENDOS NA BOVESPA - Iquiapaza, Robert Aldo; Lamounier, Wagner Moura; Amaral, Hudson Fernandes (Advances in Scientific and Applied Accounting, 2010)
The research objective was to assess the influence of asymmetric information, agency costs and property structure on the dividends payout in 178 open capital companies listed at the São Paulo stock exchange (Bovespa). The analyzed period was 2000-2004. Tobit´s regression model for censored data was used due to the fact that the payout index was censored at zero. It was verified that companies with American Depositary Receipts (ADRs) issued at the New York stock exchange, a proxy for smaller asymmetric information, paid smaller dividends, which is in line with the signalinghypothesis. After asymmetric information control, propriety concentration by the company gestors (insiders) presented a negative relationship with dividends payout. Finally, dividends payment relationship was found to be negative with opportunities for growth and positive with the cash flow, as forecasted by the pecking order hypothesis.